Electrical Resistivity and Geotechnical Attributes and The Dynamics of Foundation Vulnerability - Musa Adesola Bawallah; Stephen Olubusola Ilugbo; Kesyton Oyamenda Ozegin; Babatunde A Adebo; Isaac Aigbedion; Kazeem Adeyinka Salako (Indonesian Journal of Earth Sciences, 2021)
This research evaluates the significance of geotechnical and Electrical Resistivity methods in studying structural integrity as fundamental factors that may account for failure in a typical sedimentary environment of Ukpenu Primary School, Ekpoma, Edo State, Nigeria. Two methods were used in this study such as the Electrical Resistivity approach involving the use of Lateral Horizontal Profiling (LHP), 2D Electrical Resistivity Tomography (ERT), and Vertical Electrical Sounding (VES) techniques. While geotechnical method involved the collection of soil samples from the study locations for the characterization of the soil properties that are very vital to foundation studies. Nine VES were carried out using Schlumberger array with current electrode spacing varying from 1 to 40 m, with 2-D ERT using Dipole-Dipole electrode array with inter-station separation of 5 m and an expansion factor varied from 1 to 5 while LHP involve Wenner array with an electrode spacing of 5 m interval and was used to determine the vulnerability factors for the building sustainability. The VES interpretation results were used to determine the second-order parameters for the determination of vulnerability. The results obtained from the two methods review that both are very fundamental to foundation dynamics. However, electrical attributes were found to give better information in terms of depth, lateral extent, layer stratification, and nature of materials which make it an indispensable tool over geotechnical attributes whose depth of investigation is up to a maximum of 5 m which poses great limitation in the evaluation of structural integrity, against stress, and strain occasion by geodynamic activities that often result into fracture, crack, highly weathered formation that usually goes beyond the shallow depth of investigation. Therefore, it can be stated that resistivity attributes account for 90% of the major contributing factors that affect foundation vulnerability.